The Impact Of Organizational Culture And Internal Communication On Employee Performance At The Regional House Of Representatives Office Of East Nusa Tenggara - Heni M. Sauw; Rohani P. Dima; Jeantri K. Sanam (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to analyze the influence of organizational culture and internal communication on employee performance at the Regional House of Representatives Office of East Nusa Tenggara Province. The background of this research is based on the importance of a conducive organizational culture and effective internal communication in improving employee performance, particularly within government institutions that play a strategic role in regional governance. This research employs a quantitative approach using multiple linear regression analysis. The population consists of all employees of the Regional House of Representatives Office of East Nusa Tenggara Province, with a sample of 62 respondents selected through a saturated sampling technique. Data were collected through questionnaires that had been tested for validity and reliability, and analyzed using statistical software. The results indicate that organizational culture has a positive and significant effect on employee performance, meaning that the better the organizational culture implemented, the higher the employee performance. Furthermore, internal communication also has a positive and significant effect on employee performance, showing that open, clear, and effective communication can enhance employees’ productivity and work quality. Simultaneously, organizational culture and internal communication have a significant effect on employee performance at the Regional House of Representatives Office of East Nusa Tenggara Province. These findings suggest that efforts to improve employee performance should focus on strengthening organizational culture values and improving internal communication systems to create a harmonious and productive work environment.